Corporate Social Responsibility – Impact for Airlines & Passengers - Peter Wild (Research Developments in Science and Technology Vol. 6, 2022)
Varied business models (low-cost and network carriers) use different approaches to their external strategy and, as a result, to communication, marketing, and internal cost structure. The distinctions between the two models are examined in general, as well as in light of the current movement toward more sustainable and transparent business models, with a focus on the consumer. To analyze the perception of the two airline business models, a quantitative empirical study was done. In addition, the importance of corporate social responsibility (CSR) in the airline business was assessed, as well as an examination of shifting flyer behavior as a result of the COVID-19 issue. The link between the individual variables was evaluated using a correlative technique in this study. The study found that CSR plays a crucial role in the thinking of passengers, particularly in terms of charitable and legal obligation, and that worries about ecological responsibility gained traction during the COVID-19 pandemic. COVID-19 did not appear to generate a demand shift among business models, and there were no differences in passengers’ views of CSR among models.